1981
DOI: 10.1021/bi00507a030
|View full text |Cite
|
Sign up to set email alerts
|

Affinities of amino acid side chains for solvent water

Abstract: Equilibria of distribution of amino acid side chains, between their dilute aqueous solutions and the vapor phase at 25 degrees C, have been determined by dynamic vapor pressure measurements. After correction to pH 7, the resulting scale of "hydration potentials", or free energies of transfer from the vapor phase to neutral aqueous solution, spans a range of approximately 22 kcal/mol. The side chain of arginine is much more hydrophilic than those of the other common amino acids, with an equilibrium constant of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
623
2
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 828 publications
(660 citation statements)
references
References 36 publications
32
623
2
3
Order By: Relevance
“…j Ho  collects the hydrophobic interactions of the j-th residue with others localized within the specified distance c. Any hydrophobicity scale [47][48][49][50][51][52][53] may be applied to calculate the observed distribution of hydrophobicity. Despite some differences between hydrophobicity parameters in these scales, it was found that these differences do not significantly influence the final results [18].…”
Section: Binding Site Recognitionmentioning
confidence: 99%
“…j Ho  collects the hydrophobic interactions of the j-th residue with others localized within the specified distance c. Any hydrophobicity scale [47][48][49][50][51][52][53] may be applied to calculate the observed distribution of hydrophobicity. Despite some differences between hydrophobicity parameters in these scales, it was found that these differences do not significantly influence the final results [18].…”
Section: Binding Site Recognitionmentioning
confidence: 99%
“…The (hypothetical) standard state concentration of the amide solute is 1 M in the vapor phase as well as in the liquid phase (see Section 6.2.4). Wolfenden and coworkers next measured the transfer free energies of model compounds for amino acid side chains [98]. The ionized forms of the basic and acidic residues are excluded from their study because species containing a full formal charge interact too strongly with water to be measured.…”
Section: Solvation Free Energies Of Amidesmentioning
confidence: 99%
“…With the MSAs of exposed methylene and carboxyl groups in various carboxylic acids, AGVL may be calculated using these values (+40 and -260 cal/A2, respectively) in Equation 1 . Experimental values of AGVL may be obtained from the distribution coefficients of compounds between the vapor phase and aqueous solution, using Wolfenden's approach (Wolfenden, 1978;Wolfenden et al, 1981). A comparison between these observed and calculated values of AGVL is provided in Table 3 for several carboxylic acids.…”
Section: Transfer Free Energiesmentioning
confidence: 99%